Young architects 14 : No precedent - Somol, R.E.; Rieselbach, Anne (New York Princeton Architectural Press, 2013)
2012 marks the twenty-fifth anniversary of the Architectural League Prize for Young Designers and Architects. Each year up-and-coming architects are recognized for excellent and inspiring work. This year's theme, No Precedent, reflects the perception of young architects as a self-defining generation driven by the desire to be heard and unwilling to either wait their turn or to follow in others' footsteps. They are quick to cast aside unfit precedents, codes, and rules. Their work is suggestive, speculative, and on the brink$1 (Bneither here nor there, but fodder for the future. The projects in Young Architects 14 investigate what it takes to create something without precedent and how this influences the way designers work and what they produce.s
Keywords: BUREAU SPECTACULAR; KOJI TSUTSUI & ASSOCIATES MMX STUDIO; SOFTLAB; STPMJ; WEATHERS; ARCHITECTURE EDUCATION (AR-EDU)